نحو رؤية إستراتيجية للمحافظة على الهوية الثقافية للشباب الجزائري - برويس, وردة; دباب, زهية (جامعة الوادي - University of Eloued, 2019)
أدت العولمة الثقافية إلى إحداث تغيرات كثيرة على مستوى الهوية لدى الشباب كتشويه اللغة العربية وغياب الالتزام بتعاليم الدين،وعليه فهي أدت إلى حدوت تحديا فكريا وثقافيا خاصة لدى الشاب،نظرا لما تقدمه له القنوات الفضائية ومواقع الانترنت والهواتف المحمولة من برامج ، وأصبح يقلد كل ما يشاهده عبر هذه الوسائط،من سلوكيات سواء كانت مفيدة أو مضرة بالنسبة له، لقد جعلت هذه الوسائط الشباب يعيشون في عالم خيالي، بعيدا عن المجتمع و أسرته، مما ولد لدى الشباب مرض الإحباط واليأس من واقعه المعاش. وعليه تهدف هاته المداخلة إلى إعطاء رؤية إستراتيجية للمحافظة على الهوية الثقافية للشباب الجزائري،وبالتالي الحد من الآثار السلبية التي أثرت على هذه الهوية.من خلال تقديم اهم المفاهيم المتعلقة بالموضوع،واهم التطبيقات لإستراتيجية المحافظة على الهوية الثقافية في المجالات المختلفة سواء في العقيدة والأخلاق أو السياسية والاقتصاد أو الثقافة وأيضا تطبيقها في الجانب التربوي والعلمي Cultural globalization has led to many changes in the identity level of young people, such as distorting the Arabic language and the absence of commitment to the teachings of religion, and therefore it led to an intellectual and cultural challenge especially for the young man, given the programs provided by satellite channels, websites and mobile phones, and he imitates everything he watches. Through these media, from behaviors whether beneficial or harmful to him, these media have made young people live in an imaginary world away from society and his family, which gave young people a disease of frustration and despair from his lived reality. Accordingly, this intervention aims to give a strategic vision to preserve the cultural identity of Algerian youth, and thus limit the negative effects that have affected this identity, by presenting the most important concepts related to the topic, and the most important applications of the strategy for preserving the cultural identity in various fields, whether in creed, ethics or politics. And the economy or culture, as well as its application in the educational and scientific aspect
Towards a strategic vision to preserve the cultural identity of Algerian youth
مقال بمجلة السراج في التربية وقضايا المجتمع . مج 03 ع04. ديسمبر 2019 . جامعة الوادي
Keywords: الإستراتجية ؛ الهوية ؛ الثقافة ؛ الهوية الثقافة ؛ الشباب; Strategy; Identity; the culture ; Identity culture; Young